Tensile Behavior of Hybrid Plain Woven Fabric Laminate Repaired by Scarfing Method. Issue 9 (November 2013) - Sui, Liu; Zhidong, Guan; Xia, Guo; Jianhua, Chen; Guofen, Xi; Jing, Cai
Experimental investigation on tensile behavior of hybrid plain woven fabric laminate repaired by scarfing method was conducted in the paper. There were 3 types of specimens with scarf ratio of 1:10, 1:20 and 1:30, respectively. Tests results indicated the tensile strength of repaired laminate increasing with scarf ratio and the specimen with the scarf ratio of 1:30 has the highest tensile strength which could reach 103.2% of the intact laminate strength. Besides, distinct differences were observed on failure mode of specimens with different scarf ratio. For specimen with scarf ratio of 1:10, damage initiated and propagated in repair zone while failure occurred outside repair zone for 1:30 specimen. A finite element model was developed with ABAQUS to simulate tensile behavior of repaired specimens. The calculated results were in good agreement with test results. Based on the numerical model, influence of scarf ratio to stress distribution in adhesive, ultimate tensile strength and failure mode of repaired laminate was discussed. Results of the investigation provide insight into scarfing repair design method on hybrid plain woven fabric laminate.